Mary Ann to her Ginger: comparing the extended brand identity of two elite female athletes. Issue 4 (6th November 2017) - Lobpries, Jami; Bennett, Gregg; Brison, Natasha
Abstract : Purpose: The purpose of this paper is to compare the extended brand identities of two elite female athletes. Specifically, this exploratory case study assessed the extended brand identities of Jennie Finch and Cat Osterman, two iconic female softball athlete brands. Design/methodology/approach: Through the qualitative analysis of individual in-depth, semi-structured interviews, various documents, and social media, data revealed themes associated with positioning, personality, and presentation of the female athlete brands. Findings: Theoretically, the themes provide empirical support for existing brand identity frameworks. Practical implications: Practically, findings provide evidence for defining an athlete's extended brand identity that can serve as the foundation for branding efforts that generate long-term value during and after their sport careers. Originality/value: This case study adds to the extant literature on athlete branding and offers practical content for marketers seeking to brand female athletes.